The Relevance of Computer Science and Arabic Language Learning Technology in Supporting Arabic Language Learning from The Perspective of Israel Scheffler - Muhammad Fadli Ramadhan; Suhayib Suhayib; Ichwanul Muttaqin; Mawadda Warahmah (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2024)
Technology integration in education is becoming increasingly important in the ever-evolving digital era. Using technology as a medium to teach students will increase the competence of educators in teaching Arabic. On the other hand, technology is expected to dilute differences in learning styles, students' ability levels, distance limitations, time, and various other learning problems that are always a scourge for educators, especially Arabic-speaking educators. This study aims to determine the relevance of computer science and Arabic language learning technology in supporting Arabic language learning from the perspective of Israel Scheffler. The type of research used uses qualitative research with a case study approach. The data sample used was a lecturer majoring in Arabic Language Education, with data collection techniques using in-depth interview techniques and documentation. The data analysis technique uses three stages: displaying data, reducing data, and drawing conclusions. The study results show the importance of integrating computer science and digital technology in learning Arabic from the perspective of Israel Scheffler, who emphasizes the importance of critical and analytical thinking skills. Digital technologies, such as AI and interactive applications, have revolutionized learning methods, enabling more responsive and effective curricula and teaching methods. Collaboration between computer science experts and Arabic language educators through joint training and projects results in innovative solutions, improving teaching efficiency and enriching students' learning experience so that education remains relevant.